1992
DOI: 10.1073/pnas.89.6.2409
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure of Theiler murine encephalomyelitis virus (BeAn strain).

Abstract: Depending on the strain, Theiler murine encephalomyelitis virus (TMEV) may cause acute encephalitis or chronic demyelinating disease, which is associated with viral persistence in mice. Persistent central nervous system infection and demyelination by the less-virulent TMEV has provided a useful animal model for the human demyelinating disease multiple sclerosis. The less-virulent BeAn strain of TMEV was crystallized and its atomic structure was determined by x-ray crystallography. The a-carbon coordinates of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 23 publications
4
76
0
Order By: Relevance
“…Thus, the already known VP1 structure of Mengo virus could be used as a substitution analogy for a BJC3 VP1 molecular model. In addition, the structural comparison between Mengo virus and TMEV, a well-investigated virus for CNS disease models, showed a similar conformation of loop II (residues 94-112 in TMEV and 90-110 in Mengo virus) on the external surface of the virion [18]. Based on the reported structures for Mengo, molecular modeling analysis by Collaborative Computational Project No.…”
Section: Selection Of Animal Model and Position For Site-directed Mutmentioning
confidence: 99%
“…Thus, the already known VP1 structure of Mengo virus could be used as a substitution analogy for a BJC3 VP1 molecular model. In addition, the structural comparison between Mengo virus and TMEV, a well-investigated virus for CNS disease models, showed a similar conformation of loop II (residues 94-112 in TMEV and 90-110 in Mengo virus) on the external surface of the virion [18]. Based on the reported structures for Mengo, molecular modeling analysis by Collaborative Computational Project No.…”
Section: Selection Of Animal Model and Position For Site-directed Mutmentioning
confidence: 99%
“…Since then, structures of several other picornaviruses have been described (1,34,35,41,48,56,62,(65)(66)(67)84,85,104,112,121,122). The protein shell of the virion is composed of 60 copies of the 4 capsid proteins, VP1, VP2, VP3, and VP4, that are arranged on an icosahedral surface.…”
Section: The Virionmentioning
confidence: 99%
“…The 3-dimensional structures of several poliovirus and of several related picornaviruses have been determined at near atomic resolution by X-ray crystallographic methods (Hogle et al, 1985;Rossmann et al, 1985;Luo et al, 1987Luo et al, , 1992Acharya et al, 1988;Grant et al, 1992). These studies have shown that the major capsid proteins VPl, VP2, and VP3 share a common "core" structure, composed of a wedge-shaped 8-stranded antiparallel @-barrel, but have dissimilar connecting loops, and long dissimilar extensions at their amino-termini.…”
mentioning
confidence: 99%